PENGARUSUTAMAAN SPIRITUAL DALAM PENDIDIKAN WAWASAN KEBANGSAAN (Studi Kasus GEMA NUSA di Pesantren Daarut Tauhiid Bandung) - Said, Nur (Pascasarjana IAIN Kudus, 2014)
AbstractThe article’s main focus is on exploring the character educational model for nationalism in pesantren (Islamic boarding school) Daarut Tauhid (DT) Bandung through Gerakan Nurani Membangun Bangsa (GEMA NUSA). The article based on qualitative research through case study and phenomenological method. The results are; (1) The presence of GEMA NUSA aims to build a moral nation towards